Cultural intermediaries in the production of culture - Bulc, Gregor (Javnost-The Public, 2004)
The author supports the thesis that media and cultural studies should embrace the analysis of subjective characteristics of cultural production, that is, the analysis of individuals employed in cultural industries and mass media, who significantly determine the form and content of cultural products. The article addresses the question of how to approach cultural intermediaries, or contemporary creative workers in the (re)production cycles of symbolic goods. In earlier studies cultural intermediaries were regarded as part of a class responsible for the quick expansion of consumer capitalism and the rise of postmodern life-styles. Today, cultural intermediaries, according to the author, are a highly heterogeneous professional group, whose common denominator could hardly be found in a class habitus. Therefore, cultural intermediaries should be studied in accordance with their specific roles, values, and working and consumer habits in each culture of production.